Integrasi Tasawuf Falsafi dalam Pendidikan Agama Islam di Era Algoritma: Rekonstruksi Kurikulum Berbasis Spiritualitas Digital - Bayu Mujrimin; Zulaekah Zulaekah; Sumianti Sumianti (Mahad Al Jamiah UIN Syarif Hidayatullah Jakarta, 2026)
The rapid advancement of artificial intelligence, algorithmic systems, and big data has transformed educational practices while raising concerns about declining spiritual awareness and ethical values. Islamic Religious Education (Pendidikan Agama Islam/PAI) is therefore expected to strengthen not only digital competencies but also learners' moral and spiritual development. This study analyzes the integration of philosophical Sufism (tasawuf falsafi) into PAI as a foundation for reconstructing a digital spirituality-based curriculum in the algorithmic era. Using a qualitative library research approach, the study examines classical works of philosophical Sufism alongside contemporary literature on Islamic education and digital technology. The findings reveal that the concepts of ma'rifah, mahabbah, tazkiyat al-nafs, and insan kamil provide a philosophical framework for reinforcing learners' ethical and spiritual dimensions amid algorithmic dominance. These values can be integrated through the reformulation of educational objectives, reflective learning materials, and pedagogical practices that foster self-awareness, digital ethics, and critical reflection. This study proposes a conceptual curriculum framework that integrates technological advancement with Islamic spirituality, enabling PAI to respond more effectively to contemporary educational challenges.